Фінансові імперативи розвитку соціального захисту населення - Чугунов, І. Я.; Насібова, Ольга Вікторівна (Державний торговельно-економічний університет, 2021)
Розкрито та обґрунтовано фінансові імперативи розвитку системи соціаль ного захисту населення. Визначено склад, структуру та динаміку джерел фінансо вого забезпечення соціального захисту населення у загальних видатках на соціальний захист та валовому внутрішньому продукті протягом 2003–2019 рр. Розроблено структурно-функціональну модель фінансового забезпечення соціального захисту населення. Запропоновано пріоритети забезпечення фінансової стійкості та збалансованості системи соціального захисту населення.

In the conditions of permanent adaptive processes to modern challenges and threats of social stability there is a change in the key points of the country sustainable development, connected with strengthening in the social component of the eco nomic policy which demands search and new mechanisms application or existing activezation of the influence mechanisms on behaviour of economic subjects for supplying the social effect from the distribution and redistribution of newly created value in the society. Effectiveness, speed and duration of transformation processes in the direction of improving population welfare and economic growth in the country depends on identification of unrealized financial opportunities of social protection system, taking into account macro economic trends, demographic changes.
The financial imperatives development of the population social protection
Keywords: фінансове забезпечення; соціальний захист населення; бюджетне фінансування; соціальне страхування; благодійність; гранти; financial supply; social protection; budget financing; social insurance; charity; grants